A Peroxygenase from Chaetomium globosum Catalyzes the Selective Oxygenation of Testosterone. (1st March 2017) - Kiebist, Jan; Schmidtke, Kai‐Uwe; Zimmermann, Jörg; Kellner, Harald; Jehmlich, Nico; Ullrich, René; Zänder, Daniel; Hofrichter, Martin; Scheibner, Katrin
Abstract: Unspecific peroxygenases (UPO, EC 1.11.2.1) secreted by fungi open an efficient way to selectively oxyfunctionalize diverse organic substrates, including less‐activated hydrocarbons, by transferring peroxide‐borne oxygen. We investigated a cell‐free approach to incorporate epoxy and hydroxyl functionalities directly into the bulky molecule testosterone by a novel unspecific peroxygenase (UPO) that is produced by the ascomycetous fungus Chaetomium globosum in a complex medium rich in carbon and nitrogen. Purification by fast protein liquid chromatography revealed two enzyme fractions with the same molecular mass (36 kDa) and with specific activity of 4.4 to 12 U mg −1 . Although the well‐known UPOs of Agrocybe aegerita ( Aae UPO) and Marasmius rotula ( Mro UPO) failed to convert testosterone in a comparative study, the UPO of C. globosum ( Cgl UPO) accepted testosterone as substrate and converted it with total turnover number (TTN) of up to 7000 into two oxygenated products: the 4, 5‐epoxide of testosterone in β‐configuration and 16α‐hydroxytestosterone. The reaction performed on a 100 mg scale resulted in the formation of about 90 % of the epoxide and 10 % of the hydroxylation product, both of which could be isolated with purities above 96 %. Thus, Cgl UPO is a promising biocatalyst for the oxyfunctionalization of bulky steroids and it will be a useful tool for the synthesis of pharmaceutically relevant steroidal molecules. Abstract : Oxyfunctionalized testosterone : Cgl UPO, a novel peroxygenase from the ubiquitous ascomycetous fungus C. globosum, facilitates the direct incorporation of epoxy and hydroxy functionalities into the sterically demanding molecule testosterone. The reaction requires only hydrogen peroxide as co‐substrate. This peroxygenase and related enzymes might be useful tools for the synthesis of pharmaceutically relevant steroidal molecules.